2008
DOI: 10.1002/acp.1430
|View full text |Cite
|
Sign up to set email alerts
|

Language crimes and the cognitive interview: testing its efficacy in retrieving a conversational event

Abstract: Frequently, the only available evidence in 'language crimes' (e.g. verbal sexual harassment) is witness statements about criminal conversations. However, previous research has showed that recall for sentences in conversation is very poor. The main aim of this research was to find out how to solve this problem. The cognitive interview (CI) is an interview technique which has shown to be more effective in recalling criminal episodes than a comparison interview. In addition, our experience in research on the CI h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
21
2
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(29 citation statements)
references
References 40 publications
5
21
2
1
Order By: Relevance
“…It was also found that although there was no significant increase in the information recalled for conversation verbatim and conversation person, the CI did significantly increase the amount of conversation gist reported by the participants when compared with the SI. Campos and Alonso‐Quecuty () also found that the CI increased correct conversation gist details; however, they additionally found an increase in correct conversation verbatim details, which was not found in the present study. The discrepancy between the present study and Campos and Alonso‐Quecuty's () study may be explained by the differences in the event used.…”
Section: Discussioncontrasting
confidence: 92%
“…It was also found that although there was no significant increase in the information recalled for conversation verbatim and conversation person, the CI did significantly increase the amount of conversation gist reported by the participants when compared with the SI. Campos and Alonso‐Quecuty () also found that the CI increased correct conversation gist details; however, they additionally found an increase in correct conversation verbatim details, which was not found in the present study. The discrepancy between the present study and Campos and Alonso‐Quecuty's () study may be explained by the differences in the event used.…”
Section: Discussioncontrasting
confidence: 92%
“…The observed increased recall of conversation gist information by both adults with and without ID when interviewed using the CI is consistent with and builds upon the works of Campos & Alonso‐Quecuty () and Prescott et al . (), who both used a sample which did not included adults with ID.…”
Section: Discussionsupporting
confidence: 89%
“…(), who both used a sample which did not included adults with ID. This is important as conversation detail may be the only type of information that can lead to the successful prosecution of non‐physical crimes, such as verbal abuse (Campos & Alonso‐Quecuty ). More importantly, these results suggest that appropriate questioning of adults with ID can enhance their recall of this type of investigatively important information, therefore leading them to be considered valuable witnesses.…”
Section: Discussionmentioning
confidence: 99%
“…In the earwitness studies that have found a positive effect the critical events have been quite long in duration, 7 minutes (Memon & Yarmey, 1999) and 15 minutes respectively (Campos & Alonso-Quecuty, 2008).…”
Section: The Cognitive Interviewmentioning
confidence: 99%